Electroplated Polymer‐Modified Carbon Fiber for Performance‐Enhancing Composite Interfaces - Zeyang Yu; Xinzhang Zhou; Christopher C. Bowland; Logan T. Kearney; Holly Humphrey; Yawei Gao; Sargun Singh Rohewal; Harry M. Meyer III; Amit K. Naskar (Advanced Materials Interfaces)
Abstract Carbon fiber composite performance relies on the fiber‐matrix interface for effective load transfer. To enhance interfacial properties between the fiber and matrix, often carbon fiber surfaces are oxidatively and covalently modified to incorporate chemical functional groups. By contrast, here, noncovalent electrodeposition of functional polyelectrolyte is applied onto conducting carbon fibers from aqueous solutions. A natural polymer, chitosan (CS), is electro‐deposited onto the fiber surface, which undergoes multi‐scale physical interactions. The bound CS layer with abundant amine functionalities reacts with epoxy moieties within the matrix to improve the interfacial properties. The scalable and energy‐efficient electrodeposition eliminates traditional functionalization and sizing requirements of carbon fiber while delivering significantly higher mechanical performance with enhanced consistency. For continuous fiber reinforced composites, compared to conventional fibers, apparent interlaminar shear strength increases by 27%, reaching ≈86 MPa. The short fiber composites with only 2–11 wt.% fibers exhibit ≈20% increase in tensile strength with a peak performance of 120 MPa. Unlike traditionally treated and sized carbon fiber, this approach delivers coated fibers with long shelf‐life and allows recovery of both CS in electrolyte form and carbon fiber by continuous electrochemical processing of the modified fibers with inverse polarity; thus, it promotes overall fiber recyclability.